The Relationship between Frequency of Breastfeeding and Sexual Distress in Postpartum Women - Maryam Zamani; Robab Latifnejad Roudsari; Maryam Moradi; Habibollah Esmaili (Mashhad University of Medical Sciences, 2018)
Background & aim: Due to frequent waking at night for breastfeeding, nursing mothers are likely to suffer from sleep deprivation, which may lead to sexual dysfunction. To the best of our knowledge, few studies have been conducted on sexual distress in nursing mothers. Thus, we sought to examine the relationship between the frequency of breastfeeding and female sexual distress during postpartum period. Methods: This descriptive correlational study was conducted on 80 women aged 18-35 years, visiting healthcare centers in Mashhad, Iran, during 2016. To select the participants, multi-stage sampling method was used. The data collection tools included demographic and fertility-related questionnaire, the Depression, Anxiety, and Stress Scale-21 (DASS-21), and the Female Sexual Distress Scale-Revised (FSDS-R). To analyze the data, Kruskal-Wallis H test, Spearman's rank-order correlation, and linear regression model were run in SPSS, version 16. Results: The mean score of postpartum sexual distress in mothers was 20.43±8.00. According to the results of the Spearman's rank-order correlation, the frequency of nighttime breastfeeding was directly correlated with maternal sexual distress (P=0.010, r=0.26). However, there was no correlation between the frequency of daytime breastfeeding sessions and sexual distress (P=0.976, r=0.003). Conclusion: Considering the correlation between the frequency of breastfeeding at night and postpartum sexual distress in mothers, it seems necessary to adopt effective counselling approaches to overcome female sexual distress during this period.